Numerical verification of energy release rate and J-Integral in large strain formulation - Teng Long; Leyu Wang; Cing-Dao Kan; James D. Lee (Forces in Mechanics, 2023)
The fracture criterion is a critical topic in fracture mechanics. However, the equality of J-Integral (J) and energy release rate (G) has not been numerically verified under large strain theory. This paper aims to numerically justify the condition for equality in brittle and small-scale plastic fracture. The computation of the J in this study was performed using the commercial finite element program LS-DYNA and postprocessor LS-PrePost. The G was measured by node release method in LS-DYNA. Our result numerically verified the equality of G = J in elasticity, but not in plasticity. This is also supported by the analytical derivation. The critical energy release values in this work are considered in a reasonable range compared with experiment data. Note: The entire paper, with the exception of equations, was rephrased using ChatGPT. This was achieved by requesting ChatGPT to rewrite the original manuscript written by humans, paragraph by paragraph.